Ideias que valem a pena espalhar: ted talks e a construção ethos discursivo sob o olhar de uma Relações Públicas - Vaz, Ana Laura Motta [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
Society today has the Internet as the main communication hub. With more and more information available, those that gain prominence and recognition for their credibility deserve our attention. This the main reason why TED Talks videos were selected as the subject of this analysis. With the theoretical and methodological support of French Discourse Alalysis, we propose a study of how to construct the ethos in the TED Talks format, taking into account the ideological character of the discourse and the curatorship of the TED (Technology, Entertainment and Desig), the organization responsible for the videos. When analyzing the sample of three videos - one of the most accessed, one of the most commented and one of the most recent - we could observe that the ethos of the organization itself, present in the institucional discourses, legitimizes itself from the ones built in TED ethos. We also discussed the 'genericity' of the TED Talk format, which would fit best in the hyper genre concept of the site genre

A sociedade tem hoje a Internet como principal eixo comunicativo. Com cada vez mais informações disponíveis, aquelas que ganham destaque e reconhecimento por sua credibilidade merecem nossa atenção. Esse é o principal motivo pelo qual os vídeos TED Talks foram selecionados como objeto de análise do discurso da linha francesa, propomos um estudo de como se dá a construção do ethos no formato TED (Tecnologia, Entretenimento e Design), organização responsável pelos vídeos. Ao analisar a amostra de três vídeos - um dos mais acessados, um dos mais comentados e um dos de entrada mais recente - pudemos observar que o ethos da própria organização, presente nos discursos institucionais, se legitima a partir dos ethe construídos em seus produtos TED Talks e que esses, por sua vez, também a 'generosidade' do formato TED Talk, que se enquadraria melhor no conceito de hipergênero do gênero site
Keywords: Relações publicas; Análise do discurso; Ethos